Voice analysis in detection (Academic Journal of Internal Affairs, 2018)
The author provides an overview of how LVA (Layered Voice Analysis) voice analysis technology is applied by Hungarian law enforcement agencies to conduct a multi-level examination of the conscious and unconscious brain activity (thoughts and feelings).
Keywords: law enforcement; voice analysis; detection